192k views
3 votes
Which expression is equivalent to (4p^-4q)^-2/10pq^-3? Assume p and q do not equal 0. A. 25p^10/4q^8 B. 2q/5p^5 C. p^7q/160 D. 125p^11q/2

User Govert
by
5.2k points

2 Answers

4 votes

Answer: C.
=(p^7q)/(160) .


Step-by-step explanation: Given expression
((4p^(-4)q)^(-2))/(10pq^(-3)).

Applying exponents of exponent rule
(ab)^c = a^cb^c and

negative power rule
(a)^(n) = (1)/(a^n).


(4p^(-4)q)^(-2) = 4^(-2)p^{-4*(-2)q^(-2)} = (1* p^8)/(4^2q^2)

=
((4p^(-4)q)^(-2))/(10pq^(-3))= (1* p^8q^3)/(10* 4^2pq^2)


= ( p^8q^3)/(160pq^2)

Apply quotient rule of exponents
(a^m)/(a^n) = a^(m-n).


( p^8q^3)/(160pq^2)= (p^(8-1)q^(3-2))/(160)


=(p^7q)/(160) .

Therefore, correct option is C.
=(p^7q)/(160) .



User Matt Styles
by
6.1k points
1 vote
The equivalent expression to
(4p^-4q)^-2/10pq^-3
=(4^-2p^(-4*-2)q^-2)/(10pq^-3)
=(4^-2p^8q^-2)/(10pq^-3)
=[p^8q^-2/16]/[10pq^-3]
=p^7q/160

Answer: C]p^7q/160
User Holanda
by
6.0k points